The principle of subsidiarity and its application in European Union Law - Radivojević, Zoran; Knežević Predić, Vesna (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Abstract: The principle of subsidiarity embodies the idea of conferring a specific power to the higher level or wider community only provided that it is more effective for accomplishing the envisaged objectives than the action taken at the lower level of authority. Taken from the constitutions of some of the EU Member States, this principle was first introduced into the primary law of the European Communities, although without an explicit reference, as a guiding principle in the field of environmental protection. With the establishment of the European Union, the subsidiarity principle has substantially developed, both as a main principle of political organisation for the EU and as a governing principle in the exercise of non-exclusive powers which are conferred to the EU. The Lisbon Treaty has retained the principle of subsidiarity in both aforementioned forms, but it extends the scope of its application to all areas of the EU activities, including the former second and the third pillar. Concurrently, it establishes mechanisms which enable the implementation and continuous monitoring of the application of the subsidiarity principle in the process of adopting legislative acts. It is actually a mechanism that ensures ex ante control, which entails an early warning system involving the scrutiny of national parliaments of Member States. On the other hand, the judicial or ex post control is carried out by the Court of Justice in the process of judicial review, on the basis of filed actions for annulment on the ground of violation of the subsidiarity principle. In addition to the Members States, the applicants authorized to initiate this proceeding are also the national parliaments, their chambers or the Committee of the Regions.